Effect of long-term Tai Chi training on Parkinson’s disease: a 3.5-year follow-up cohort study - Li, Gen; Huang, Pei; Cui, Shishuang; He, Yachao; Tan, Yuyan; Chen, Shengdi (Journal of neurology, neurosurgery and psychiatry, 2024)
BackgroundTai Chi has shown beneficial effects on the motor and non-motor symptoms of Parkinson’s disease (PD), but no study has reported the effect of long-term Tai Chi training.ObjectiveTo examine whether long-term Tai Chi training can maintain improvement in patients with PD.MethodsCohorts of patients with PD with Tai Chi training (n=143) and patients with PD without exercise as a control group (n=187) were built from January 2016. All subjects were assessed at baseline and in November 2019, October 2020 and June 2021. A logarithmic linear model was used to analyse rating scales for motor and non-motor symptoms. The need to increase antiparkinsonian therapies was presented as a Kaplan–Meier plot and as a box plot. The bootstrap method was used to resample for statistical estimation.ResultsTai Chi training reduced the annual changes in the deterioration of the Unified Parkinson’s Disease Rating Scale and delayed the need for increasing antiparkinsonian therapies. The annual increase in the levodopa equivalent daily dosage was significantly lower in the Tai Chi group. Moreover, patients benefited from Tai Chi training in motor symptoms, non-motor symptoms and complications.ConclusionTai Chi training has a long-term beneficial effect on PD, with an improvement in motor and non-motor symptoms and reduced complications.Trial registration number NCT05447975.